2015
DOI: 10.3109/0284186x.2015.1043026
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of lactate dehydrogenase in solid tumors: A systematic review and meta-analysis of 76 studies

Abstract: Background. In cancer cells, metabolism is shifted to aerobic glycolysis with lactate production coupled with a higher uptake of glucose as the main energy source. Lactate dehydrogenase (LDH) catalyzes the reduction of pyruvate to form lactate, and serum level is often raised in aggressive cancer and hematological malignancies. We have assessed the prognostic value of LDH in solid tumors. Material and methods. A systematic review of electronic databases was conducted to identify publications exploring the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(195 citation statements)
references
References 102 publications
4
180
0
1
Order By: Relevance
“…In recent clinical trials, elevated serum LDH has been shown as an independent predictor of overall survival in advanced or metastatic cancer of the breast (Brown et al, 2012), prostate (Scher et al, 2009;Gravis et al, 2014), colorectum (Bar et al, 2014), oesophagus (Polee et al, 2003), pancreas (Tas et al, 2001), ovary (Schneider et al, 1998), nasopharynx (Jin et al, 2013), gastric adenocarcinoma (Sougioultzis et al, 2011), hepatocellular carcinoma (HCC) (Faloppi et al, 2014), renal cell carcinoma (Armstrong et al, 2012) and melanoma (Balch et al, 2004;Weide et al, 2012). The inverse association with overall survival in solid tumours were shown in a recent meta-analysis, with HR for overall death of 1.7 (95% CI: 1.62-1.79) (Petrelli et al, 2015). Nevertheless, a marked publication bias was observed, with most of smaller studies reporting only positive associations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In recent clinical trials, elevated serum LDH has been shown as an independent predictor of overall survival in advanced or metastatic cancer of the breast (Brown et al, 2012), prostate (Scher et al, 2009;Gravis et al, 2014), colorectum (Bar et al, 2014), oesophagus (Polee et al, 2003), pancreas (Tas et al, 2001), ovary (Schneider et al, 1998), nasopharynx (Jin et al, 2013), gastric adenocarcinoma (Sougioultzis et al, 2011), hepatocellular carcinoma (HCC) (Faloppi et al, 2014), renal cell carcinoma (Armstrong et al, 2012) and melanoma (Balch et al, 2004;Weide et al, 2012). The inverse association with overall survival in solid tumours were shown in a recent meta-analysis, with HR for overall death of 1.7 (95% CI: 1.62-1.79) (Petrelli et al, 2015). Nevertheless, a marked publication bias was observed, with most of smaller studies reporting only positive associations.…”
Section: Discussionmentioning
confidence: 93%
“…Complete follow-up was obtained and all laboratory measurements were performed in the same laboratory (Holme et al, 2010). Although a number of studies have indicated the association between LDH and overall survival (Petrelli et al, 2015), this is the first populationbased study linking baseline LDH and cancer-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent past, the role of LDH as a prognostic factor and as a marker for treatment response has been confirmed further. In a meta-analysis of 76 studies on the prognostic role of LDH in solid tumors, including 12 melanoma studies from 1998 to 2014, Petrelli and colleagues confirmed that high serum LDH concentration is associated with lower overall survival in melanoma patients (9). Recent studies analyzed the suitability of serum LDH as marker for outcome of advanced melanoma patients after treatment with immunomodulatory drugs.…”
Section: Biomarkers In Malignant Melanoma: a Current Statusmentioning
confidence: 95%
“…Here, patients with high S100B levels showed a shorter progression-free disease (55). In patients with lesions of Breslow thickness >1 mm, Swiss and German guidelines recommend S100B quantification every 3-6 months for the first 1-5 years, and every 6-12 months for years [6][7][8][9][10]. Serum concentration appears to correlate with Breslow thickness and tumor burden measured under RECIST (Response Evaluation Criteria In Solid Tumors) 1.1 (8).…”
Section: S100 Proteinsmentioning
confidence: 99%
“…Szolid daganatos páciensek körében 76 vizsgálatban (n = 22 882) a kiindulási medián LDH 245 U/l értéket meghaladó esetekben a teljes túlélés rosszabb volt (HR 1,7 [95%-os CI 1,62-1,79], p<0,00001) [108]. Egy másik, szolid daganatos páciensek körében végzett elemzés szerint, 68 vizsgálatban (n = 31 857) az emelkedett kiindulási LDH (>250 U/l) rosszabb teljes túléléssel társult (HR 1,48 [95%-os CI 1,43-1,53], p<0,00001) [109].…”
Section: Metaanalízisekunclassified